Caspase-1 Is an Apical Caspase Leading to Caspase-3 Cleavage in the AIM2 Inflammasome Response, Independent of Caspase-8. Issue 2 (19th January 2018) - Sagulenko, Vitaliya; Vitak, Nazarii; Vajjhala, Parimala R.; Vince, James E.; Stacey, Katryn J.
Abstract: Canonical inflammasomes are multiprotein complexes that can activate both caspase-1 and caspase-8. Caspase-1 drives rapid lysis of cells by pyroptosis and maturation of interleukin (IL)-1β and IL-18. In caspase-1-deficient cells, inflammasome formation still leads to caspase-3 activation and slower apoptotic death, dependent on caspase-8 as an apical caspase. A role for caspase-8 directly upstream of caspase-1 has also been suggested, but here we show that caspase-8-deficient macrophages have no defect in AIM2 inflammasome-mediated caspase-1 activation, pyroptosis, and IL-1β cleavage. In investigating the inflammasome-induced apoptotic pathway, we previously demonstrated that activated caspase-8 is essential for caspase-3 cleavage and apoptosis in caspase-1-deficient cells. However, here we found that AIM2 inflammasome-initiated caspase-3 cleavage was maintained in Ripk3 −/−  Casp8 −/− macrophages. Gene knockdown showed that caspase-1 was required for the caspase-3 cleavage. Thus inflammasomes activate a network of caspases that can promote both pyroptotic and apoptotic cell death. In cells where rapid pyroptosis is blocked, delayed inflammasome-dependent cell death could still occur due to both caspase-1- and caspase-8-dependent apoptosis. Initiation of redundant cell death pathways is likely to be a strategy for coping with pathogen interference in death processes. Graphical Abstract: Highlights: Inflammasomes activate a network of caspases to initiate pyroptosis and apoptosis. Caspase-1 and caspase-8 are the inflammasome apical caspases. AIM2 inflammasome activates caspase-1 independent of caspase-8. Caspase-1 and caspase-8 are both upstream of caspase-3 cleavage initiated by AIM2. Redundant death pathways may combat pathogen evasion strategies.